Steel slag as sulfate-reducing bioreactor filler to promote sulfate reduction and manganese removal from acid mine drainage - Haixia Wang; Zhitao Zhang; Mingliang Zhang; Yishun Zhao; Yu Zhang; Hui Wang (Desalination and Water Treatment, 2025)
Efficient sulfate reduction and manganese (Mn) removal from acid mine drainage (AMD) using sulfate-reducing bioreactor (SRBR) remains challenging. Filler is an important factor affecting the operation performance of SRBR. In this study, the effectiveness of steel slag as a filler in SRBR for the treatment of AMD was compared with the commonly used limestone in terms of sulfate reduction and Mn removal. The results showed that steel slag improved the efficiency of sulfate reduction and Mn removal compared to limestone in both static batch test (sulfate: 51.24 %-84.46 % vs 47.13 %-81.58 %; Mn: 84.16 %-97.29 % vs 70.13 %-94.98 %) and continuous flow SRBR (sulfate: 81.31 % vs 69.87 %; Mn: 22.55 % vs 15.34 %). The microbial oxidation and recovery of the sulfides produced from SRBR was also investigated, and complete oxidation of sulfide and inhibition rate of sulfate reformation (>87 %) was achieved by micro-aeration, reducing the secondary production of sulfate and providing the potential opportunity for elemental sulfur (S0) recovery. Microbial co-occurrence network analysis revealed that microorganisms in SRBR-steel slag could use ecological niche overlap and cooperation to achieve better performance. It suggested that steel slag could be used as a substitute for the commonly used limestone in the SRBR filler for AMD treatment.